Study on typography and colour for Galeri Shah Alam signage / Tuan Nur Afiqah Tuan Faaeh - Tuan Faaeh, Tuan Nur Afiqah (2019)
Galery Shah Alam is located at Persiaran Seksyen 14 40000 Shah Alam Selangor. Inspired by Raja Muda Selangor in the middle of 1989. Currently, Gallery Shah Alam is hosting Pameran Terbuka. Every month, Gallery Shah Alam is doing an exhibition. The artwork will be exhibit in gallery 1 and 2. The purpose of Gallery Shah Alam is to bring cultural and artistic activities to help young painters and art exhibitors showcase their artwork. However, gallery Shah Alam fail to attract the young generation especially art and design student. Gallery Shah Alam also has a problem with the signage system, which leads to less attraction from them. Signage is one of the important elements in wayfinding. It should be located in a public place to show direction. In this research. I would like to study the suitable design element, such as typography, layout and colour that can attract the young generation. Typography and colour are one of the elements of design. It is very important in design, especially in graphic design fields. As a graphic design student, typography and colour must be part of the study and design.